2018
DOI: 10.18510/ijsrtm.2018.615
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Critical Factors for Delay in Metro Rail Projects in India

Abstract: Purpose of the study:World over, transportation infrastructure projects face delays in commissioning and India is no exception. This study is carried out with an objective to specifically identify the critical delay factors in the commissioning of metro rail projects in India. Methodology: A questionnaire survey was conducted to identify the major causes of delay from the opinion of clients, contractors and consultants. Calculation of Relative Importance Index (RII) for the shortlisted factors yielded th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…It cannot be ignored" (Taroun, 2014). Risks are classified as per their allotment as well as from their source of origin (Mittal and Paul, 2018). The identified and categorized risks have been assessed by various methods in the literature such as Monte-Carlo simulations (Purnus and Bodea, 2014), Analytical Hierarchical Process (AHP) (Taroun, 2014), vague set theory (Yan et al, 2019), Bayesian Belief Network (Luu et al, 2009) etc.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…It cannot be ignored" (Taroun, 2014). Risks are classified as per their allotment as well as from their source of origin (Mittal and Paul, 2018). The identified and categorized risks have been assessed by various methods in the literature such as Monte-Carlo simulations (Purnus and Bodea, 2014), Analytical Hierarchical Process (AHP) (Taroun, 2014), vague set theory (Yan et al, 2019), Bayesian Belief Network (Luu et al, 2009) etc.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Evidently, out of close to 1,200 km of metro lines all over India, 79% are elevated while only 21% are underground. Many of these metro projects have faced severe delays in construction and implementation over the past few years (Mittal and Paul, 2018), similar to many construction projects in other developing countries (Shehu et al, 2014). However, compared with most other construction projects, the time overrun costs of metro projects are significantly higher owing to large amounts of capital investments in metro rail construction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results also indicated that delays in the provision of necessary materials and financial problems were the main reasons for the delays in this project (Aswathi & Thomas, 2013). Mittal and Paul (2018) also investigated the reasons for delays in the construction of urban railway projects in India.…”
Section: Causes Of Delay In Railway Development Projectsmentioning
confidence: 99%
“…Delays in land ownership and delivery of the project site to the contractors, changes in applications and possible requirements, delayed payments, unpredictable underground effects and changes in the ground conditions, raw material shortage in the market, delays in approval of the project design and decision-making, lack of sufficient workforce, lack of adequate data collection and incomplete investigations before implementation, and delays in acquisition of necessary permits were identified as the most important reasons for delays in these projects (Mittal & Paul, 2018).…”
Section: Causes Of Delay In Railway Development Projectsmentioning
confidence: 99%